Active mobility in residential areas. - (:unkn) unknown (My University, 2013)
Cycling traffic and the urban neighbourhood mutually strengthen each other as both become increasingly important. Shorter distances make cycling more attractive for day-to-day travel. Conversely, everyday mobility that is geared to cycling helps making the residential environment more attractive and increase the demand, for example, for nearby shopping and leisure facilities. In that context it is also important not to forget that high cycling and walking levels already make for an attractive and vivid urban character of the street environment and thus the residential neighbourhood. Active travel such as cycling is very much a part of residents experience and their everyday life. (Difu)
Keywords: Individualverkehr; Fahrradverkehr; Verkehrsplanung; Fahrradweg; Fahrradinfrastruktur; Radverkehrsanlage; Radverkehrsplanung